The Living and Adaptation of the Homosexual Conscript Soldiers in a Military Camp - Khengsuntia, Kelvaly; Sanguanpauk, Khemika (Journal of Roi Et Rajabhat University, 2022)
The purposes of this research were to study the living and adaptation of the homosexual conscript soldiers in a military camp in Lopburi. This research was qualitative research. The study method was storytelling. The informants consisted of 4 homosexual conscript soldiers, a friend of them and a trainer, the total was 6 informants. The informants were selected by purposive sampling. The data were collected by semi-structured interviews with non-participation observation. The results revealed that the technology of self-affecting the homosexual conscript soldiers can live and adapt to a military camp was 1) Voluntary adaptation to various situations in a military camp, 2) Encouragement from themselves, trainers and other conscript soldiers and 3) Creating a new identity by loving himself and overcoming their fear. These will lead to the creation of identity and be sociable. This research suggests that 1) military camp should publicize about no gender discrimination or bullying the homosexual conscript soldiers, and 2) to provide a trainer and conscript soldiers understand homosexual conscript soldiers to adjust the attitude on homosexual conscript soldiers.